Power point as an audiovisual didactic resource to enhance efl learninig at the eighth level of San Francisco high school - Vivar, Alexandra; Vásquez, Diana
This project pretends to determine if Power Point is an audiovisual didactic resource that can enhance ELF learning. Specifically, this project tries to show that the use of Power Point can benefit the students` language comprehension. It also tries to demonstrate that the integration of Power Point is an alternative for English learning. The students who got involved in this project are at the eighth level of San Francisco High School. They are from 12 to 15 years old. They take English classes five hours a week and use an English book. This project was carried out in two ways, the first one was a traditional class and the second one was a class using Power Point. We developed some topics which were related to the students´ age such as greetings and introductions, personal information, and commands. Through the worksheets, we evaluated students´ learning which helped us to analyze the data. The results obtained showed a generally positive motivation of students towards learning English through the use of Power Point. Based on this study, it could be concluded that the use of Power Point made the English class interesting and motivated students to develop a positive attitude towards learning English. Finally, this project suggests that English teachers can incorporate the use of Power Point to teach as a way to add variety into classroom procedures, so students do not get bored. It could be a form of motivation for the students and also for teachers.